DELAYED DISCHARGE IN VETERANS AFFAIRS NURSING HOMES. (11th November 2018) - Mills, W L; Ying, J; Kunik, M E
Abstract: Recent VA policies have focused on minimizing time residents spend in Community Living Centers (CLCs; VA nursing homes). Little is known about characteristics of residents who remain beyond the ideal of 90 days. Examining Minimum Data Set assessments of all VA CLC admissions between 1/1/2009 and 6/30/2012 (n=35, 114) we found 7, 883 residents remained beyond 90 days. Generalized linear mixed models identified predictors of discharge timeframe using facility as a random effect. Characteristics of residents who remained beyond 90 days were black race, financial power of attorney, greater dependence in activities of daily living, previous stay in a facility, and diagnosis of dementia or schizophrenia. Unique characteristics of those who remained beyond 365 days were older age, cancer diagnosis, cognitive impairment, and prior assisted living stay. Our findings provide information to help with decision-making regarding admission to the CLC and to develop interventions to improve discharge to the community.